Teratogenic effect of 1.3 bis (p-Hydroxyphenyl)urea on Wistar rats (Rattus norvegicus L.) - Denny Satria; Ziza Putri Aisyia Fauzi; Urip Harahap; Yuandani; Syukur Berkat Waruwu; Hari Purnomo (Pharmacia, 2024)
Pain is a physiological disorder that pregnant women often experience, so they take various medications to relieve the pain. Many pain relievers on the market have teratogenic effects on pregnant women. 1.3 bis(p-Hydroxyphenyl)urea is a modification of p-aminophenol and has analgesic and anti-inflammatory properties and fewer hepatotoxic side effects. However, its safety in pregnant women has not been studied. This research continues our previous research to determine the teratogenic effects on white rat fetuses and toxic effects on pregnant white rats after administering 1.3 bis(p-Hydroxyphenyl)urea. The teratogenic effect test was carried out on pregnant rats divided into five groups with doses of 50, 500 and 1000 mg/kg BW, CMC Sodium 0.5%, and Gabapentin 50 mg/kg BW as the control group. Rats marked as pregnant were given test preparations and observed for toxic symptoms, and then fetal weight, body length, internal malformations and bone malformations were observed surgically. The study showed that administration at 50 and 500 mg/kg BW doses did not have a teratogenic effect. However, at a dose of 1000 mg/kg BW, it causes teratogenic effects characterized by fetal bleeding and bone abnormalities.